Ultrasound-guided continuous costoclavicular block through retrograde stimulating catheter technique for postoperative analgesia in shoulder surgery: a case series - Sandeep Diwan; Divya Sethi; Parag Sancheti; Abhijit Nair (Brazilian Journal of Anesthesiology, 2023)
In five patient undergoing surgery for proximal humerus fracture we investigated into postoperative analgesia provided by continuous costoclavicular block using continuous stimulating catheter. The postoperative pain scores were less than 4 in all patients except in two patients who required intravenous tramadol 50 mg as a rescue analgesic. The radiocontrast dye study executed in two patients revealed contiguous contrast spread through the brachial plexus sheath with the catheter tip in the interscalene space. We propose that a continuous costoclavicular block with a retrograde stimulating catheter is a feasible alternative regional anesthesia technique for postoperative analgesia in shoulder surgery.